MAKNA DAN ARTI IKLAN ROKOK - Ni Ketut Sukanti (Majalah Ilmiah Widyacakra, 2019)
Ads from the past, now and in the future make the most effective weapon for communicating to the public both social and commercial through print and electronic media, one of the advertisements that we often see and hear is cigarette advertisements using the word "Go Head". There are some creative advertisements that are displayed by the public who understand the meaning but there are still some who hang up, thus inviting the public to think more deeply about the mean and meanings of words or sentences contained in advertisements. But with the Semiotics approach, which is the science of sign and signified, we can and can give meaning and meaning to the word Go Head or "form of resistance" from: 1) educative from the government to the public that smoking can damage health but on the other hand The government needs funds for the development process from the receipt of retribution and cigarette taxes, so the go head can be interpreted ok, 2). In terms of competition between industries and cigarette users, users do not need to be confused and are advised to use it continuously, 3) there is a restricted area or no-smoking area but a sign that the road continues.